2010
DOI: 10.1016/j.neuron.2010.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Dixdc1 Is a Critical Regulator of DISC1 and Embryonic Cortical Development

Abstract: Summary The psychiatric illness risk gene Disrupted in Schizophrenia-1 (DISC1) plays an important role in brain development, however, it is unclear how DISC1 is regulated during cortical development. Here, we report that DISC1 is regulated during embryonic neural progenitor proliferation and neuronal migration through an interaction with DIX domain containing-1 (Dixdc1), the third mammalian gene discovered to contain a Disheveled-Axin (DIX) domain. We determined that Dixdc1 functionally interacts with DISC1 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
127
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(129 citation statements)
references
References 51 publications
2
127
0
Order By: Relevance
“…Our studies in mouse hippocampi and in C. elegans motor neurons together also show that DISC1 plays a role in regulating axonal connections (9). Because DISC1 is involved in essentially all aspects of neurodevelopment (4-7, 11), and because more than a dozen cytosolic proteins are reported to interact with DISC1 (6, 8,[28][29][30], it is likely that DISC1 acts as a scaffold protein inside neurons, recruiting various signaling components to exert its specific function at different developmental stages. It is therefore not surprising that, in contrast to our results, DISC1 has recently been reported to interact with another RAC1-GEF, Kalirin-7, and to inhibit the RAC1 signaling during dendritic spine morphogenesis (31).…”
Section: Discussionmentioning
confidence: 52%
“…Our studies in mouse hippocampi and in C. elegans motor neurons together also show that DISC1 plays a role in regulating axonal connections (9). Because DISC1 is involved in essentially all aspects of neurodevelopment (4-7, 11), and because more than a dozen cytosolic proteins are reported to interact with DISC1 (6, 8,[28][29][30], it is likely that DISC1 acts as a scaffold protein inside neurons, recruiting various signaling components to exert its specific function at different developmental stages. It is therefore not surprising that, in contrast to our results, DISC1 has recently been reported to interact with another RAC1-GEF, Kalirin-7, and to inhibit the RAC1 signaling during dendritic spine morphogenesis (31).…”
Section: Discussionmentioning
confidence: 52%
“…As DISC1 regulates neurogenesis and neuronal migration, we hypothesized that aberrant neuronal distribution in the cortex may be due to DISC1-mediated effects on both processes (Kamiya et al, 2005;Mao et al, 2009). It was recently shown that DISC1 may participate in neurogenesis and neuronal migration via separate and distinct signaling pathways (Singh et al, 2010). Abnormal cortical cytoarchitecture may also result from malfunctioning of the cytoskeletal machinery mediating neuronal migration.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental evidence is accumulating for the role of DISC1 in neuronal proliferation and neuronal migration (Kamiya et al, 2005;Mao et al, 2009;Singh et al, 2010). We therefore examined the number of neurons throughout the neocortex along the medial-lateral axis.…”
Section: Fewer Neun-positive Neurons In Q31l and L100p (؊/؊) Mutant Micementioning
confidence: 99%
“…Additionally, ASPM overexpression, like many Wnt-activating components, is associated with increased cell proliferation and tumor development, supporting a common effect on proliferation (Kouprina et al 2005;Hagemann et al 2008;Klaus and Birchmeier 2008;Lin et al 2008;Bikeye et al 2010;Vulcani-Freitas et al 2011). On the other hand, decreased expression of the schizophrenia risk gene Disc1 or its binding partner, Dixdc1, results in diminished Wnt signaling activity with accompanying deficits in embryonic and adult cortical neurogenesis (Mao et al 2009;Singh et al 2010).…”
mentioning
confidence: 94%